PENGARUH ROLLING MASSAGE PUNGGUNG TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU NIFAS - Heny Ekawati (UNUSA Press, 2017)
The postpartum period is the beginning of lactation. New born babies should be able to suckle to his mother, but what happens in the field early in the postpartum period baby is difficult to suckle to his mother. Primary survey data on the first week of the postpartum period found 75% show that his milk is not yet fluent. The purpose of this study was to determine the effect of rolling back massage to increase milk production in postpartum mothers. Design of this study uses quasi experimental method with time series approach. With consecutive sampling technique. The samples are 30 respondents with control group. An instrument used is observation sheet of baby’s urine frequency first until third days. Data analysis using repeated anova test.Based on the results of this study on the babys urine frequency on control group had a mean of 5.8. While the mean of intervention group was 7.3. The results of statistical tests using Repeated Anova test,  = 0.001 ( <0.05) which means there is the effect of rolling back massage to increase milk production in postpartum mothers. Based on the results of these studies it is known that the back rolling massage can be used as an alternative to increase milk production in postpartum mother in BPS, Puskesmas or Hospital.